Penerapan Pelayanan Kantor Urusan Agama di Kecamatan Batang Kuis - Isma Azizah Dasopang; Melliana Fitri; MHD Irwansyah Rangkuti; Hapni Sartika Siregar; Dewi Safitri; Fadma Utami; Cindi Lusia Afosma; Haryanti Putri; Shylvia Mahfira; Mahlaini Rambe; Solihun Azim; Fitriani Fitriani (JIE (Journal of Islamic Education), 2022)
The purpose of writing this article is to determine the application of the Office of Religious Affairs (KUA) services in Batang Kuis. This study uses a qualitative method with a case study approach. The research location is KUA Batang Kuis, Deli Serdang. The Office of Religious Affairs (KUA) is also part of a government institution providing direct services to the community. KUA is the central work unit in the Ministry of Religion because KUA directly deals with the district. Therefore, it is natural that the existence of KUA is considered very important, along with the presence of the Ministry of Religion. Besides that, KUA is also the face of the Ministry of Religion in the region, especially in the Batang Kuis District. Using a qualitative approach, this study found that the KUA in Batang Kuis District must serve the community regarding marriage, endowments, reconciliation, population and development of the sakinah family, and zakat and guidance to the mosque, by the policies established by applicable laws and regulations.